Efficient N-arylation of amines catalyzed by Cu-Fe-hydrotalcite - Jadhav, Vinod H.; Dumbre, Deepa K.; Phapale, Vilas B.; Borate, Hanumant B.; Wakharkar, Radhika D. (Catalysis Communications, 2007)
An efficient N-arylation of amines with aryl halides in presence of heterogeneous recyclable Cu-Fe-hydrotalcite catalyst has been developed. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: amines; Aryl halides; Cu-Fe-hydrotalcite; heterogeneous catalyst; N-arylation

Greener ullmann-type coupling of aryl halides for preparing biaryls using reusable Pd/ZrO2 catalyst - Dumbre, Deepa K.; Wakharkar, Radhika D.; Choudhary, Vasant R. (Synthetic Communications, 2011)
Biaryls with excellent yields can be prepared by the Ullmann-type coupling of aryl halides in the presence of potassium carbonate (as a base) and dimethylformamide (as a solvent), at 140 degrees C, using a reusable Pd (2.5wt%)/ZrO2 catalyst. The product yield of 4-iodoanisole coupling is strongly influenced by the catalyst preparation method, solvent, and base.
Keywords: Aryl halides; Biaryls; Pd; Ullmann coupling reaction; ZrO2

Thermally decomposed Cu-Fe-hydrotalcite. a novel highly active catalyst for o-arylation of naphthol and phenols by aryl halides - Choudhary, Vasant R.; Dumbre, Deepa K.; Yadav, P. N.; Bhargava, Suresh Kumar (Catalysis Communications, 2012)
A novel, efficient and environmentally benign method has been reported for the synthesis of diaryl ethers by the o-arylation of napthol or phenols with aryl halides in dimethylformamide (as a solvent) under reflux, using a novel heterogeneous catalyst (having redox properties), obtained from thermal decomposition of Cu-Fe at 600 degrees C in the absence of externally added base. The catalyst comprises Cu(II) and Fe(III) species (oxides and hydroxides), which are uniformly distributed during the catalyst formation. The catalyst can be easily separated from the reaction mixture, simply by filtration and reused several times without a significant loss of its activity. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Aryl halides; C-O cross coupling reaction; Cu-Fe-hydrotalcite; Naphthol; o-Arylation; Phenols

Suzuki-Miyaura cross-coupling reaction between aryl halides and phenylboronic acids over gold nano-particles supported on MgO (or CaO) and other metal oxides - Dumbre, Deepa K.; Yadav, P. N.; Bhargava, Suresh Kumar; Choudhary, Vasant R. (Journal of Catalysis, 2013)
Gold nano-particles-supported alkaline earth metal oxides, particularly MgO or CaO, show high catalytic activity in the Suzuki-Miyaura cross-coupling reaction in the presence of K2CO3 and DMF (as a solvent). The catalytic activity is strongly influenced by the nature or type of metal oxide support (viz, alkaline earth oxide, Group IIIA metal oxide, transition metal oxide, or rare earth oxide actinide oxide). It is also strongly influenced by the nature of aryl halide (aryl iodide, bromide, chloride, or fluoride), amount of K2CO3 in the reaction mixture and catalyst calcination temperature. Influence of reaction parameters viz, temperature and time and different substituents in aryl halides and/or phenylboronic acids on the biphenyl product yield in the reaction over Au/MgO catalyst has also been investigated. The catalyst showed excellent reusability in the reaction. Moreover, it is ligand-free and also has much lower cost than the commonly used homogeneous and heterogeneous Pd catalysts. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: Aryl halides; Au/MgO (or CaO) catalyst; Biphenyls; Gold nano-particles; phenylboronic acids; Suzuki-Miyaura coupling reaction